2010
DOI: 10.1016/j.neuroscience.2010.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Localization of dopamine- and cAMP-regulated phosphoprotein-32 and inhibitor-1 in area 9 of Macaca mulatta prefrontal cortex

Abstract: The actions of dopamine D1 family receptors (D1R) depend upon a signal transduction cascade that modulates the phosphorylation state of important effector proteins, such as glutamate receptors and ion channels. This is accomplished both through activation of protein kinase A (PKA) and the inhibition of protein phosphatase-1 (PP1). Inhibition of PP1 occurs through PKA-mediated phosphorylation of DARPP-32 or the related protein inhibitor-1 (I-1), and the availability of DARPP-32 is essential to the functional ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 73 publications
2
9
0
Order By: Relevance
“…Moreover, the staining pattern supports the conclusion that the DARPP-32 is present in dopaminoceptive neurons, i.e., neurons that receive a dopamine input, and that it is absent from the dopaminergic neurons themselves [Ouimet et al, 1984[Ouimet et al, , 1992Schalling et al, 1990]. In particular, the protein was primarily detected in the neostriatum [Ouimet et al, 1984[Ouimet et al, , 1992Gustafson and Greengard, 1990;Ouimet and Greengard, 1990;Anderson and Reiner, 1991;Barbas et al, 1993;Greengard et al, 1998;Wang et al, 2004;Ishikawa et al, 2007;Glausier et al, 2010], and a striatal prevalence of the protein has been also confirmed in birds [Absil et al, 2001;Schnabel et al, 1997;Durstewitz et al, 1998;Reiner et al, 1998;Roberts et al, 2002;Bálint et al, 2004;Reiner et al, 2004;Metzger et al, 2006;Bálint and Csillag, 2007;Csillag et al, 2008]. In addition, studies in reptiles confirmed a pattern of distribution largely comparable among all amniotes [Smeets et al, 2001[Smeets et al, , 2003Moreno et al, 2010].…”
supporting
confidence: 75%
See 2 more Smart Citations
“…Moreover, the staining pattern supports the conclusion that the DARPP-32 is present in dopaminoceptive neurons, i.e., neurons that receive a dopamine input, and that it is absent from the dopaminergic neurons themselves [Ouimet et al, 1984[Ouimet et al, , 1992Schalling et al, 1990]. In particular, the protein was primarily detected in the neostriatum [Ouimet et al, 1984[Ouimet et al, , 1992Gustafson and Greengard, 1990;Ouimet and Greengard, 1990;Anderson and Reiner, 1991;Barbas et al, 1993;Greengard et al, 1998;Wang et al, 2004;Ishikawa et al, 2007;Glausier et al, 2010], and a striatal prevalence of the protein has been also confirmed in birds [Absil et al, 2001;Schnabel et al, 1997;Durstewitz et al, 1998;Reiner et al, 1998;Roberts et al, 2002;Bálint et al, 2004;Reiner et al, 2004;Metzger et al, 2006;Bálint and Csillag, 2007;Csillag et al, 2008]. In addition, studies in reptiles confirmed a pattern of distribution largely comparable among all amniotes [Smeets et al, 2001[Smeets et al, , 2003Moreno et al, 2010].…”
supporting
confidence: 75%
“…References: teleost: Robra and Thirumalai [2016]; lungfishes: González and Northcutt [2009]; present results; amphibians: López et al [2010]; O'Connell et al [2010]; reptiles: Smeets et al [2001Smeets et al [ , 2003; Moreno et al [2010]; birds: Schnabel et al [1997]; Durstewitz et al [1998]; Reiner et al [1998]; Absil et al [2001]; Roberts et al [2002]; Bálint et al [2004]; Reiner et al [2004]; Metzger et al [2006]; Bálint and Csillag [2007]; Csillag et al [2008]; mammals: Ouimet et al [1984Ouimet et al [ , 1992; Ouimet and Greengard [1990]; Gustafson and Greengard [1990]; Anderson and Reiner [1991]; Perez and Lewis [1992]; Barbas et al [1993]; Greengard et al [1998]; Wang et al [2004]; Ishikawa et al [2007]; Glausier et al [2010]; Buesa et al [2016]. …”
Section: Spinal Cordmentioning
confidence: 66%
See 1 more Smart Citation
“…Expression of PP1 (T320A) substantially I-1 a strong candidate for inhibiting PP1 activity in those tissues. However, I-1 is not expressed in high levels in hippocampus where it is present in the dentate gyrus, albeit at low levels (Allen et al, 2000), and it was shown, by immuno-EM studies along with DARPP-32, not to be preferentially localized in synaptic spines (Glausier et al, 2010). We found that in cortical neurons only a very small fraction of I-1 was phosphorylated at T35, the form of I-1 that can inhibit PP1 potently.…”
Section: Pp1 Dephosphorylation At T320 Is Mediated Via Auto-dephosphomentioning
confidence: 59%
“…Previous immunohistochemical studies have analyzed the distribution of DARPP-32 in the brain of mammals (Gustafson and Greengard, 1990;Ouimet et al, 1984Ouimet et al, , 1992Ouimet and Greengard, 1990;Anderson and Reiner, 1991;Barbas et al, 1993;Greengard et al, 1998;Wang et al, 2004;Ishikawa et al, 2007;Glausier et al, 2010), birds (Schnabel et al, 1997;Durstewitz et al, 1998;Reiner et al, 1998;Absil et al, 2001;Roberts et al, 2002;Bá lint et al, 2004;Reiner et al, 2004;Metzger et al, 2006;Bá lint and Csillag, 2007;Csillag et al, 2008) and reptiles (Smeets et al, , 2003. Many of these studies were mainly focused on the basal ganglia and only a few works have analyzed the distribution of DARPP-32 in regions outside the telencephalic basal ganglia and their related mesencephalic structures (Ouimet et al, 1984(Ouimet et al, , 1992Schalling et al, 1990;Perez and Lewis, 1992;Smeets et al, 2001Smeets et al, , 2003Metzger et al, 2006).…”
Section: Introductionmentioning
confidence: 99%